PENGARUH PENILAIAN KINERJA DAN REWARD TERHADAP KINERJA KARYAWAN PADA PT. JALUR NUGRAHA EKAKURIR PEKANBARU - Ulfa, Amalia; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine how much influence the performance assessment and reward to employee performance at PT. Pekanbaru Nugraha Ekakurir Line. The sample in this study were 43 respondents and the method used by census method is that the entire population is used as a sample. The data in this study uses the survey method through a questionnaire filled by employees. Data obtained from the questionnaire and then processed to then be tested using SPSS statistics. The results of analysis using simple linear regression analysis, multiple linear regression analysis, determination test (R2), individual significance test (Uj t), and similtan significant test (F test) so that it can be seen that the performance appraisal variables affect employee performance variables, reward variables effect on employee performance, and performance appraisal variables, reward variables simultaneously affect the performance variables of employees. The calculation results are known as R Square is the coefficient of determination and the R Square value is 0.770. This means that performance and reward assessments affect employee performance by 77%Keywords: Performance Assessment, Reward, Employee Performance